Falling off the treatment wagon: Barriers to cancer treatment and care for people experiencing health and social inequities. Issue 28 (1st October 2022) - Bourgeois, Amber; Mollison, Ashley; Horrill, Tara C; Lambert, Leah; Stajduhar, Kelli
Abstract : 135 Background: A key pillar of Canada's healthcare system is universal access, yet significant barriers to cancer services remain for those impacted by health and social inequities (e.g., poverty, homelessness, racism). For this reason, cancer is diagnosed at a later stage, resulting in worse patient outcomes, a reduced quality of life, and at a higher cost to the healthcare system. Those who face significant barriers to access are under-represented in cancer control services Consequently, these inequities result in people dying from cancers that are highly treatable and preventable, however; little is known about their treatment and care course. The aim of this study was to explore barriers to accessing cancer treatment among people experiencing health and social inequities within a Canadian context. Methods: We conducted a secondary analysis of ethnographic data informed by critical theoretical perspectives of equity and social justice. The original research draws from 30 months of repeated interviews (n = 147) and 300 hours of observational fieldwork with people experiencing health and social inequities at the end-of-life, their support persons, and service providers. Results: Our analysis identified four themes presenting as 'modifiable' barriers to inequitable access to cancer treatment: (1) housing as a key determinant for cancer treatment (2) health literacy and 'missing the window' for shared decision making (3) invisibility of the social/structural determinants of health (4) navigating a complex and fractured system. These inter-related themes point to how people impacted by health and social inequities are at times 'dropped' out of the cancer system and therefore unable to access cancer treatment. Conclusions: Findings make visible the contextual and structural factors contributing to inequitable access to cancer treatment within a publicly funded health care system. Identifying people with social and health inequities and approaches to delivering cancer services are explicitly equity-oriented are urgently needed.